Do firms always want to learn from corporate venture capital investments? - Jacobs, Charlotte (2015)
In this paper, the learning intentions and outcomes for corporate venture capital are questioned. Through qualitative research in the oil and gas sector, we identified a desire to control the direction and pace of innovation as the main driver for this type of investments. A new model and framework for CVC are presented. Contrary to the traditional model of CVC, which features a dyadic relation between corporate investor and venture entrepreneur, our model shows that CVC investments create a more complex conjoint of relations between multiple stakeholders. These relations challenge the neo-Schumpeterian model of competition. Using the grounded theory approach, we created a theoretical framework explaining and predicting outcomes of corporate venture capital other than learning. At firm level, our framework conceptualizes CVC programs as dynamic capabilities, and suggests a competitive advantage for the corporate investor through its ability to faster and better integrate the new technology. At market level, we proposed that CVC investments positively affect the pace of innovation in the market through an increased speed of acceptance of technologies supported by corporate investors.